THE EFFECT OF AUDITORS' EXPERIENCE, WORKLOAD PRESSURE, AND GENDER ON AUDIT QUALITY - Narti Eka Putri; Syifa Fauziah (JURNAL MITRA MANAJEMEN, 2023)
This study aims to analyze the relationships between Auditor's Experience, Workload Pressures, and Gender on Audit Quality. The method used is the survey method with the correlational approach. At the same time, the research data was obtained from instruments distributed to 110 auditors who worked at a public accounting firm in South Jakarta and listed on the Financial Service Authority. In addition, the statistical testing result in the first hypothesis showed that Auditors' Experience has a significant effect on Audit Quality, and the second hypothesis showed that Workload Pressure does not affect Audit Quality. In contrast, Gender does not have a significant effect on Audit Quality. The F-test showed that Auditors' Experience, Workload Pressure, and Gender simultaneously affect the Audit Quality Keywords:  Auditors’ Experience, Workload Pressure, Gender, Audit Quality, Public Accounting Firm.